Low‐intensity kangaroo grazing has largely benign effects on soil health. (9th March 2021) - Eldridge, David J.; Ding, Jingyi; Travers, Samantha K.
Summary: Kangaroos ( Macropus spp., Osphranter spp.) are the most ubiquitous free‐ranging herbivores in Australia. Much has been written on their impacts on plant community composition and how they interact with livestock, particularly in extensive rangelands. Little is known, however, about how kangaroos affect soil function and their relationship with healthy soils, nor the impact of peri‐urban populations of kangaroos where they might come into conflict with humans. To address this, we used exclosures to examine the impacts of low densities of kangaroos on the morphology of the soil surface in a peri‐urban environment on the outskirts of Sydney, Australia. We found that kangaroo grazing was associated with reduced herbaceous biomass and cover, and biocrust cover, and surfaces were generally more stable, had a greater cover and incorporation of litter and had greater plant species richness compared to inside the exclosures. There were no differences in indices of nutrient cycling nor stability. Overall, our study supports the notion that kangaroo grazing, at the current low densities experienced in this peri‐urban reserve, has had no significant deleterious effect on soil surface health, as measured by the morphology of the surface. We conclude that grazing at the current low levels (˜70 kangaroos km −2 ) is unlikely to have major long‐term negative effects on soil surface condition.